THE SPEAKING COMPREHENSTION PROBLEM AT SMP ULUMUL QUR’AN MEDAN - Wulandari, Cynthia; Ningshih, Sry Rahayu; Nainggolan, Gindo Tua; Purnama, Rizki Omilia; Harianto II, Harianto II (PHILOLOGY Journal of English Language and Literature, 2025)
Speaking skill considered in this study is the communication skill that students acquire to communicate, express opinions, convey information to others, and understand communication content. Speaking is one of the most important language abilities to acquire, and the integration of other language abilities shows how important speaking is. By assisting pupils in expanding their vocabulary and grammar, it improves the reinforcement of other abilities. Students can communicate their thoughts and feelings, tell tales, make requests, engage in dialogue, and exhibit a variety of linguistic abilities through speaking exercises. Speaking is a useful skill that allows students to convey, defend, and explain their ideas. Additionally, speaking proficiency is defined as the ability to produce words, phrases, and sentences.